Yoongoorrookoo: The emergence of ancestral personhood. Issue 3 (3rd July 2021) - RiverOfLife, Martuwarra; Pelizzon, Alessandro; Poelina, Anne; Akhtar-Khavari, Afshin; Clark, Cristy; Laborde, Sarah; Macpherson, Elizabeth; O'Bryan, Katie; O'Donnell, Erin; Page, John
ABSTRACT: Since the momentous release of the Montecristi Constitution of Ecuador in 2008, which recognised Nature, or Pacha Mama, as a subject of rights, the rights of Nature movement across the world has gained exponential momentum, with numerous jurisdictions worldwide now recognising some form of legal subjectivity vested upon Nature. In particular, since 2017, river personhood has dominated news headlines around the world as one of the most recognisable forms of Nature's novel subjectivity. The emergence of legal personhood for nature, however, has been far from uncontroversial, and numerous critiques have been advanced against the use of such a legal category – traditionally applied to humans and their abstract creations (such as States and corporations) – to the natural world, resulting in numerous calls for an alternative category of legal personhood (one that some rights of Nature advocates have termed an 'environmental person'). Against the backdrop of this emerging debate, this paper acknowledges the work undertaken by the Martuwarra Fitzroy River Council (Martuwarra Council), which was established in 2018 in the Kimberley region of Western Australia by six independent Indigenous nations to preserve, promote and protect their ancestral River from ongoing destructive 'development'. The Council believes it is time to recognise the pre-existing and continuing legal authority of Indigenous law, or 'First Law', in relation to the River, in order to preserve its integrity through a process of legal decolonisation. First Law differs markedly from its colonial counterpart, as its principles are not articulated in terms of rules, policies and procedures, but rather through stories. This paper, therefore, begins with a dialogical translation of one First Law story relating to Yoongoorrookoo, the ancestral serpent being, to create a semantic bridge between two apparently distant legal worldviews. A dialogical comparative analysis is then followed to posit and explore the concept of an 'ancestral person' as a novel comparative tool that may be able not only to capture the idea of Nature as a legal subject, but also complex Indigenous worldviews that see Nature – in this case instantiated in the Martuwarra – as an ancestral being enmeshed in a relationship of interdependence and guardianship between the human and the nonhuman world. To instantiate and embody such relationships, the paper directly, and somewhat provocatively, acknowledges the River itself, the Martuwarra RiverOfLife, as the primary participant in such dialogue, an embodied non-human co-author who began a conversation then left to human writers to continue.